2016
DOI: 10.3390/ijms17030363
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Metabolism in Bacterial Pathogenesis and Cancer Therapy

Abstract: Antibacterial resistance to infectious diseases is a significant global concern for health care organizations; along with aging populations and increasing cancer rates, it represents a great burden for government healthcare systems. Therefore, the development of therapies against bacterial infection and cancer is an important strategy for healthcare research. Pathogenic bacteria and cancer have developed a broad range of sophisticated strategies to survive or propagate inside a host and cause infection or spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 139 publications
(230 reference statements)
1
90
0
2
Order By: Relevance
“…l ‐arginine metabolism is emerging as a crucial factor in complex processes involving metabolic‐reprogramming, such as those related to biofilm formation, immune response and cancer . l ‐arginine is at the crossroads of complex metabolic networks that enable P. aeruginosa to utilize this amino acid as a source of carbon, energy, and nitrogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…l ‐arginine metabolism is emerging as a crucial factor in complex processes involving metabolic‐reprogramming, such as those related to biofilm formation, immune response and cancer . l ‐arginine is at the crossroads of complex metabolic networks that enable P. aeruginosa to utilize this amino acid as a source of carbon, energy, and nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, in P. aeruginosa l ‐Arginine is at the crossroads of multiple anabolic and catabolic/energy pathways, particularly under anaerobic conditions, thus widening the metabolic versatility of this bacterium. l ‐arginine metabolism is emerging as a crucial factor in complex biological processes involving metabolic‐reprogramming, such as those related to bacterial biofilm formation and virulence, immune response and cancer . Interestingly, recent data suggest that l ‐arginine is perceived and catabolized by bacteria during infection to escape the host defense strategies by (i) changing the pH (due to the ammonium production) and (ii) contrasting the iNOS‐mediated nitric oxide production, (by depleting the host of the iNOS substrate, ie, l ‐Arginine) …”
Section: Introductionmentioning
confidence: 99%
“…Lyme spirochetes lack the full spectrum of homologs of four different pathways that have been characterized in other bacterial systems for catabolism of the polyamine precursor Arg, i.e., the (i) arginase, (ii) arginine deiminase (ADI), (iii) arginine succinyltransferase (AST), and (iv) arginine transaminase pathways; however, some members of the ADI pathway are present, such as ArcA (BB0841; arginine deiminase), ArgF (BB0842; ornithine carbamoyltransferase), and ArcD (BB0843; arginine/ornithine antiporter) (40). ArcA is the first enzyme that converts arginine to citrulline with the release of the NH 3 molecule.…”
Section: Figmentioning
confidence: 99%
“…In addition, it has been reported to reduce the pathogenicity of herpes simplex and influenza viruses, probably due to compromised function of proteins in the envelope . The functions of Arg has revealed that it is in involved in the regulation of immune cells in cancer, inflammation, infections, etc …”
Section: Introductionmentioning
confidence: 99%
“…In particular, Arg metabolism has been illustrated to be important not only for bacterial pathogenesis but also for cancer therapy. Therefore, greater understanding of Arg metabolism in pathogenic bacteria and cancer cells would provide possible targets for controlling bacterial infections and possible cancer treatment . Therefore, the effect of Arg in treating many developmental and health problems offers great promise for improved health of living beings …”
Section: Introductionmentioning
confidence: 99%